Fi in Gulf Pidgin Arabic - Potsdam, Eric; Alanazi, Mohammad (Kansas Working Papers in Linguistics, 2014)
Gulf Pidgin Arabic (GPA) is a simplified communication system established by the non-Arabic immigrants to Gulf countries in the Middle East. In the past decades, millions of people with no Arabic skills have come from countries such as Bangladesh, India, Indonesia, Pakistan and the Philippines for job opportunities. They needed to try to speak Arabic in order to communicate with their employers and this communication system has evolved into a pidgin. GPA is based on Gulf Arabic (GA), the variety of Arabic spoken in the Gulf states: Bahrain, Oman, Qatar, United Arab Emirates, Kuwait, and nearby areas.